The impact of foreign workers on labour productivity in Malaysian manufacturing sector - Mohd Noor, Zaleha; Isa, Noraini; Said, Rusmawati; Abd Jalil, Suhaila (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
The growing presence of foreign workers in Malaysia can be explained by excess demand for labour combine with rapid economic growth, as well as the cheaper cost of foreign workers. Besides, industrialization also brought the foreign workers into Malaysia. Thus, when the foreign workers enter the labour force, they have many possible outcomes on labour market issues and productivity. This study determines the impact of foreign workers on labour productivity. Besides, the relationship between domestic and foreign workers as well as their contribution on Malaysian Manufacturing sector growth also investigated. The Cobb-Douglas production function is used to derive the model specification in this study. The results in this study show that foreign labours have positive and significant impact on labour productivity. Further, the study also reveals that foreign labours are neither substitutes nor complements for domestic labours.